Ecological Wood Anatomy of Pinus roxburghii in Central Nepal - Joshi, Lajmina; Chalise, Pratikshya (Journal of Plant Resources, 2022)
Pinus roxburghii Sarg. is a gymnosperm tree belonging to the family Pinaceae having extensive distribution in Bangladesh, Bhutan, China (Tibet), India, Nepal and Pakistan. In Nepal, it is found in subtropical region at an elevational range from 500 to 2700 m asl. The aim of the present study is to determine the ecological variation in wood characters and non-anatomical characters such as diameter at breast height (DBH), tree height and altitude. Nine wood block samples were collected from the outermost part of the trunk of three matured canopy trees at three different localities between 1100 and 1350 m above sea level from central Nepal. Correlation and regression analysis were carried out to study variation in wood anatomical characters. Multiple regression analysis was done using non-anatomical factors as independent variables and anatomical features as dependent variables. Quantitative wood characters were found to be affected by change in ecological factors but not on its qualitative wood characters. Tracheids length as well as tracheid’s pit significantly varies with altitude. A weak correlation was found between wood anatomical characters and non-anatomical parameters. Tracheids length exhibited negative correlation whereas tracheids pit exhibits positive correlation with altitude. Since tracheids are the main conducting tissues in xylem of pines, decreasing length and increasing pit size of tracheids is of ecological importance. This study will help in identifying how wood characters are adapted in response to change in ecological factors as well as help to predict ecological factor disturbances.